ENVIROMENTAL INSIGHT IN UCIL THE MOUSE DEER FAIRY TALE COLLECTION WRITTEN BY TRIA AYU K (An Ecocritic Study) - Nanik Setyowati; Emzir Emzir (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
ABSTRACT The connection of nature with literary works raises concepts about ecological problems in literature among literary critics. Many environmental problems that occur at this time. Through poetry, fairy tales and other literary works, the writers mention this in their works. Ecocritic has a basic paradigm that every object can be seen in ecological networks, and ecology can be a helpful science in this critical approach. Environmental insight can be obtained through a literary work. Some writers in Indonesia make nature and the environment a prominent part of their works. In addition to literary works such as poetry and novels, fairy tales have first explored nature. In fairy tales, nature is described as the place of life of the characters. That way, fairy tales indirectly invite the audience to come into contact with environmental insights that need to be studied and applied in everyday life. Keywords: environmental insight ; ecocritic; fairy tale; literary studies